A Colonial Southern Bookshelf Reading in the Eighteenth Century - Kerrison, Catherine (Mercer University Lamar Memorial Lectures, 1979)
A Colonial Southern Bookshelf studies popular books among southern readers in eighteenth-century America. From booksellers' lists and sale catalogs, Richard Beale Davis's study focuses on three key groups of literature: books in law, politics, and history; books on religious topics; and belles lettres. His examination of the colonial southern library suggests many revealing conclusions: persons of many social and economic levels owned and read books; literacy was more widespread than many historians have perceived; the vast majority of the books in southern libraries were published in England and Europe; and colonial newspapers constituted an important influence on cultural tastes. A Colonial Southern Bookshelf takes a historical look at the popular reading lists of the time and what they say about society in eighteenth-century America. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.